Wave-absorbing material as well as preparation method and application thereof
By combining the sponge matrix, MXene material and natural rubber to form a continuous structure of the wave absorbing material, the problem of insufficient absorption effect of the existing wave absorbing materials in the wide band is solved, and efficient electromagnetic wave absorption and good mechanical properties are achieved, which is suitable for wide band applications in the 6G era.
Patent Information
- Application Number
- CN202411673495.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The existing wave absorbing materials have insufficient absorption effect in wide bands, which is difficult to meet the demand for wide band wave absorbing materials in the 6G era. At the same time, their use in high-energy-density microwave environments may have an adverse impact on human health.
The wave absorbing layer and reflective layer prepared including a sponge matrix, MXene material and natural rubber are connected by MXene material to form a continuous structure to improve the absorption rate of electromagnetic waves, and the mechanical strength and stability of the material are enhanced by the combination of natural rubber and MXene material.
It provides wave absorbing materials with high electromagnetic shielding performance and good mechanical properties, which can effectively absorb electromagnetic waves in a wide frequency band, maintain stability in special environments, and reduce potential risks to human health.
Smart Images

Figure CN119521641A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wave absorbing materials, and in particular to a wave absorbing material and a preparation method and application thereof. Background Art
[0002] With the rapid development of communication technology, especially the upcoming 6G era, the electromagnetic environment has become increasingly complex. 6G technology not only pursues higher data transmission rates and lower latency, but also strives to achieve wider spectrum coverage, including applications in high-frequency bands such as the terahertz band. However, the wavelength of electromagnetic waves in high-frequency bands is extremely short, easily blocked by obstacles, and susceptible to environmental reflection and interference during propagation, which poses a severe challenge to the stability and efficiency of communication systems. Therefore, it is particularly important to develop materials that can effectively absorb and reduce electromagnetic wave reflection.
[0003] In the field of electromagnetic wave absorption, absorbing sponge, as a special electromagnetic wave absorbing material, has been widely used in many fields such as electromagnetic compatibility testing, electromagnetic field protection, antenna design, noise control, etc. Although traditional absorbing sponges have good absorbing effects within a certain frequency band, their absorbing frequency band is often narrow, which makes it difficult to meet the demand for wide-band absorbing materials in the 6G era. In addition, with the increase in base station density and the continuous increase in electromagnetic energy, long-term exposure to high-energy-density microwave environments may have adverse effects on human health, which further emphasizes the importance of developing efficient wide-band absorbing materials.
[0004] Specifically, the absorbing sponges on the market are mostly made of organic polymer materials such as silicone, chloroprene rubber, and polyurethane, and ferrite, carbon black, iron oxide and other absorbers are added to improve the absorbing performance. These materials show good absorbing effects in specific frequency bands, but have obvious deficiencies in wide frequency bands. For example, although the flat absorbing material has a simple structure, the absorbing frequency band is narrow; although the pyramidal absorbing material can achieve broadband absorption, its structure is complex and easy to wear and deform, which is not conducive to practical application. In addition, in recent years, research in the field of absorbing materials has also made certain progress. For example, some studies have used the combination of quantum materials and semiconductor materials to enhance the quantum effect of materials by reducing the dimension, thereby improving the absorbing performance. However, although these new materials have potential, their preparation process is complex and costly, and their stability and reliability in practical applications still need to be further verified.
[0005] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, an object of the present invention is to provide an absorbing material and a preparation method and application thereof, aiming to solve the problem that the existing absorbing materials are deficient in absorbing waves in a wide frequency band.
[0007] The technical solution of the present invention is as follows:
[0008] In a first aspect of the present invention, there is provided an absorbing material, the absorbing material comprising an absorbing layer and a reflecting layer, the absorbing layer being prepared from a sponge matrix, a MXene material and natural rubber, and the reflecting layer being prepared from a MXene material and natural rubber;
[0009] Wherein, the absorbing layer and the reflecting layer are connected by MXene material.
[0010] Preferably, the absorbing layer is prepared from a sponge matrix with a mass fraction of 90% to 95%, a MXene material with a mass fraction of 7.5% to 10%, and a natural rubber with a mass fraction of 0% to 2.5%.
[0011] Preferably, the reflective layer is prepared from 75% by mass of MXene material and 25% by mass of natural rubber.
[0012] Preferably, the thickness of the wave absorbing layer is 1 mm to 20 mm, and the thickness of the reflective layer is 5 μm to 500 μm.
[0013] A second aspect of the present invention provides a method for preparing an absorbing material, comprising the following steps:
[0014] A solution containing a MXene material is mixed with a natural rubber solution to obtain a first mixed solution, and then a sponge matrix is immersed in the first mixed solution to obtain a wet sponge matrix containing a MXene material and natural rubber, which is recorded as an absorbing layer;
[0015] The solution containing the MXene material is mixed with the natural rubber solution to obtain a second mixed solution, and then the second mixed solution is filtered, and the filtration is stopped when the second mixed solution just disappears to obtain a wet film, which is recorded as a reflective layer;
[0016] The wave absorbing layer is placed on the surface of the reflective layer to obtain a wave absorbing material precursor, and the wave absorbing material precursor is subjected to a pressing process and a drying process in sequence to obtain the wave absorbing material.
[0017] Preferably, in the first mixed solution, the mass ratio of MXene material to natural rubber is 3:1.
[0018] Preferably, the sponge matrix is immersed in the first mixed solution for 10 minutes.
[0019] Preferably, in the second mixed solution, the mass ratio of MXene material to natural rubber is 3:1.
[0020] Preferably, the temperature of the drying treatment is 60° C., and the time of the drying treatment is 1 to 12 hours.
[0021] The third aspect of the present invention provides the use of the above-mentioned absorbing material or the absorbing material prepared by the above-mentioned preparation method in the field of electromagnetic wave absorption.
[0022] Beneficial effects: The present invention provides an absorbing material and its preparation method and application. The present invention combines the high conductivity and high electromagnetic shielding performance of MXene materials with the porous structure of the sponge matrix, so that the provided absorbing material has both high electromagnetic shielding efficiency and good mechanical properties. In addition, the absorbing layer and the reflecting layer of the absorbing material provided by the present invention are connected by MXene materials. The continuous structure ensures a high absorption rate of electromagnetic waves on the one hand, and adjusts the impedance matching characteristics at the interface on the other hand, further improving its absorption rate of electromagnetic waves. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a flow chart of the absorbing material prepared by the preferred embodiment of the present invention.
[0024] Figure 2 The absorbing material prepared in Example 1 of the present invention is used to demonstrate its flexibility.
[0025] Figure 3 This is an electron microscope scanning image of the absorbing material prepared in Example 1 of the present invention.
[0026] Figure 4 It is a graph showing electromagnetic shielding testing of the absorbing materials prepared in Examples 1-4 of the present invention and Comparative Example 1.
[0027] Figure 5 This is a comparative test chart of electromagnetic shielding of the absorbing materials prepared by Examples 1-4 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0028] The present invention provides an absorbing material and a preparation method and application thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0029] An embodiment of the present invention provides an absorbing material, the absorbing material comprising an absorbing layer and a reflecting layer, the absorbing layer being prepared from a sponge matrix, a MXene material and natural rubber, and the reflecting layer being prepared from a MXene material and natural rubber;
[0030] Wherein, the absorbing layer and the reflecting layer are connected by MXene material.
[0031] The present invention combines the high conductivity and high electromagnetic shielding performance of MXene materials with the porous structure of the sponge matrix, so that the provided absorbing material has both high electromagnetic shielding effectiveness and good mechanical properties. In addition, the absorbing layer and the reflecting layer of the absorbing material provided by the present invention are connected by MXene materials. This continuous structure ensures a high absorption rate of electromagnetic waves on the one hand, and adjusts the impedance matching characteristics at the interface on the other hand, further improving its absorption rate of electromagnetic waves.
[0032] In addition, the absorbing layer and the reflecting layer provided by the present invention are both made of MXene materials and natural rubber. The natural rubber and the MXene material will form new chemical bonds after being combined. The combination of the two, on the one hand, enhances the binding force of the components in the absorbing material, thereby enhancing the mechanical strength of the absorbing material, and on the other hand, improves the stability of the absorbing material in special environments, such as water.
[0033] In some embodiments, the absorbing layer is prepared from a sponge matrix with a mass fraction of 90% to 95%, a MXene material with a mass fraction of 7.5% to 10%, and a natural rubber with a mass fraction of 0% to 2.5%.
[0034] In some preferred embodiments, the absorbing layer is prepared from a sponge matrix with a mass fraction of 92%, a MXene material with a mass fraction of 6%, and a natural rubber with a mass fraction of 2%.
[0035] In some preferred embodiments, the absorbing layer is prepared from a sponge matrix with a mass fraction of 90%, a MXene material with a mass fraction of 7.5%, and a natural rubber with a mass fraction of 2.5%.
[0036] In some embodiments, the reflective layer is prepared by including 75% by mass of MXene material and 25% by mass of natural rubber.
[0037] In some embodiments, the absorbing layer has a thickness of 1 mm to 20 mm, and the reflective layer has a thickness of 5 μm to 500 μm.
[0038] In some preferred embodiments, the thickness of the absorbing layer is 5 mm, and the thickness of the reflecting layer is 5 μm.
[0039] In some preferred embodiments, the thickness of the absorbing layer is 10 mm, and the thickness of the reflecting layer is 10 μm.
[0040] By adopting the above mass ratio and thickness, a lighter shielding and absorbing material with better flexibility can be obtained, which can be suitable for more application scenarios.
[0041] The present invention provides a method for preparing the above-mentioned absorbing material, comprising the following steps:
[0042] A solution containing a MXene material is mixed with a natural rubber solution to obtain a first mixed solution, and then a sponge matrix is immersed in the first mixed solution to obtain a wet sponge matrix containing a MXene material and natural rubber, which is recorded as an absorbing layer;
[0043] The solution containing the MXene material is mixed with the natural rubber solution to obtain a second mixed solution, and then the second mixed solution is filtered, and the filtration is stopped when the second mixed solution just disappears to obtain a wet film, which is recorded as a reflective layer;
[0044] The wave absorbing layer is placed on the surface of the reflective layer to obtain a wave absorbing material precursor, and the wave absorbing material precursor is subjected to a pressing process and a drying process in sequence to obtain the wave absorbing material.
[0045] In some embodiments, in the first mixed solution, the mass ratio of MXene material to natural rubber is 3:1.
[0046] In some embodiments, the sponge matrix is immersed in the first mixed solution for 10 minutes.
[0047] In some embodiments, in the second mixed solution, the mass ratio of MXene material to natural rubber is 3:1.
[0048] In some preferred embodiments, the drying temperature is 60° C., and the drying time is 1 to 12 hours.
[0049] In some embodiments, the drying temperature is 60° C., and the drying time is 2 hours.
[0050] The embodiments of the present invention also provide application of the above-mentioned absorbing material in the field of electromagnetic wave absorption.
[0051] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments, and are only for illustrating the present invention but not limiting the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0052] Preparation Example 1
[0053] The preparation of MXene nanosheets includes the following steps:
[0054] MXene nanosheets are prepared by chemical etching and intercalation stripping. The specific operation is as follows: take 12mL of deionized water in a plastic bottle with a pipette, and stir the plastic bottle magnetically at 35°C. Then take 24mL of 9M HCl and 5mL of HF and add them to the stirred plastic bottle to obtain a mixed solution. Then weigh 2g of Ti3AlC2 powder and slowly add it to the mixed solution in small amounts several times, and stir and etch for 24h at a temperature of 35°C. After etching, pour the mixed solution into a centrifuge tube, centrifuge at 5000rpm for two minutes, pour out the supernatant and retain the precipitate, add deionized water and continue centrifugation, repeat this operation, test with PH paper until it is neutral, remove the supernatant and retain the precipitate. Then weigh 2g of LiCl in a new plastic bottle, continue heating and stirring at 35°C, then flush the above-mentioned neutral precipitate with 120mL of deionized water into the plastic bottle containing LiCl, and continue stirring and intercalating at 35°C for 4h. The intercalated suspension was transferred into a 50 mL centrifuge tube and centrifuged at 5000 rpm for 2 min. The supernatant was discarded and the precipitate was retained. Deionized water was added and manually shaken to continue washing and centrifugation. The operation was repeated twice. The shaken mixture was then centrifuged at 8000 rpm for 3 min. Deionized water was added and shaken to continue centrifugation at 3500 rpm for 2 min. The upper suspension was placed in a new centrifuge tube to obtain MXene nanosheets.
[0055] Example 1
[0056] Preparation of absorbing materials, such as Figure 1 As shown, the following steps are included:
[0057] Preparation of the wave absorbing layer: Cut the polyurethane sponge into a size of 3cm*3cm*2mm, repeatedly wash and dry in anhydrous ethanol and deionized water. Then, use the MXene nanosheets prepared in Example 1 to prepare a MXene solution with a concentration of 0.5mg / mL, and take 20mL in a small beaker and stir magnetically, then take 1mL of natural rubber NR (30mg / mL) in a beaker and mix and stir with the MXene solution for 10min to obtain a first mixed solution, then put the polyurethane sponge into the beaker containing the first mixed solution, and put it into a vacuum drying oven for vacuum immersion for 10min to obtain a moist polyurethane sponge matrix containing MXene material and natural rubber, and obtain a wave absorbing layer.
[0058] Preparation of the reflective layer: 2.57 mL of MXene solution (10 mg / mL) prepared from the MXene nanosheets prepared in Example 1 was taken into a 50 mL beaker and magnetically stirred. Then, 200 mL of a natural latex solution with a concentration of 30 mg / mL was prepared with 61 wt% NR, and 2 mL of the 30 mg / mL natural latex solution was taken into the above-mentioned beaker containing the MXene solution and continued to stir for 15 min. After the stirring was completed, a vacuum filtration device was used to form a film. When the second mixed solution just disappeared, the filtration treatment was stopped to obtain a wet film with a MXene content of 30 wt%, and a reflective layer was obtained.
[0059] Preparation of absorbing material: The absorbing layer is neatly placed on the reflective layer and pressed evenly, and then placed in an oven and dried at 60°C for 2 hours to obtain the absorbing material. According to the MXene concentration and the 30wt% MXene content in the composite film, the absorbing material is recorded as MR3P0.5.
[0060] Example 2
[0061] Preparation of the absorbing material: The method of this embodiment is basically the same as that of Embodiment 1, except that in the preparation of the absorbing layer, the concentration of the MXene solution is 1 mg / mL, and the absorbing material prepared in this way is recorded as MR3P1.
[0062] Example 3
[0063] Preparation of the absorbing material: The method of this embodiment is basically the same as that of Example 1, except that in the preparation of the absorbing layer, the concentration of the MXene solution is 5 mg / mL, and the absorbing material prepared in this way is recorded as MR3P5.
[0064] Example 4
[0065] Preparation of the absorbing material: The method of this embodiment is basically the same as that of Example 1, except that in the preparation of the absorbing layer, the concentration of the MXene solution is 10 mg / mL, and the absorbing material prepared in this way is recorded as MR3P10.
[0066] Comparative Example 1
[0067] A method for preparing a wave absorbing material is as follows: 2.57 mL of a MXene solution (10 mg / mL) prepared from the MXene nanosheets prepared in Example 1 is placed in a 50 mL beaker and subjected to magnetic stirring, then 200 mL of a natural latex solution with a concentration of 30 mg / mL is prepared with NR having a solid content of 61 wt%, and 2 mL of the 30 mg / mL natural latex solution is placed in the above-mentioned beaker containing the MXene solution, and stirring is continued for 15 min. After stirring, a vacuum filtration device is used to form a film to obtain a film with a MXene content of 30 wt%, which is recorded as MR3.
[0068] Performance testing experiment
[0069] The flexibility of the absorbing material prepared in Example 1 is demonstrated. Figure 2 shown.
[0070] The absorbing material prepared in Example 1 was scanned by electron microscope. Figure 3 shown.
[0071] The electromagnetic shielding test was performed on the absorbing materials prepared in Examples 1-4 and Comparative Example 1. Figure 4 As shown, the black, blue and red rectangular columns in the figure represent the material's contribution to the reflection, absorption and transmission attenuation of electromagnetic waves respectively.
[0072] The electromagnetic shielding comparison test was carried out on the absorbing materials prepared in Examples 1-4 and Comparative Example 1. Figure 5 shown.
[0073] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A wave absorbing material, characterized in that: The absorbing material comprises an absorbing layer and a reflecting layer, wherein the absorbing layer is prepared from a sponge matrix, a MXene material and natural rubber, and the reflecting layer is prepared from a MXene material and natural rubber; Wherein, the absorbing layer and the reflecting layer are connected by MXene material.
2. The absorbing material according to claim 1, characterized in that: The wave absorbing layer is prepared from a sponge matrix with a mass fraction of 90% to 95%, a MXene material with a mass fraction of 7.5% to 10%, and a natural rubber with a mass fraction of 0% to 2.5%.
3. The absorbing material according to claim 1, characterized in that: The reflective layer is prepared from MXene material with a mass fraction of 75% and natural rubber with a mass fraction of 25%.
4. The absorbing material according to claim 1, characterized in that: The thickness of the wave absorbing layer is 1 mm to 20 mm, and the thickness of the reflective layer is 5 μm to 500 μm.
5. A method for preparing a wave absorbing material, characterized in that: The following steps are involved: A solution containing a MXene material is mixed with a natural rubber solution to obtain a first mixed solution, and then a sponge matrix is immersed in the first mixed solution to obtain a wet sponge matrix containing a MXene material and natural rubber, which is recorded as an absorbing layer; The solution containing the MXene material is mixed with the natural rubber solution to obtain a second mixed solution, and then the second mixed solution is filtered, and the filtration is stopped when the second mixed solution just disappears to obtain a wet film, which is recorded as a reflective layer; The wave absorbing layer is placed on the surface of the reflective layer to obtain a wave absorbing material precursor, and the wave absorbing material precursor is subjected to a pressing process and a drying process in sequence to obtain the wave absorbing material.
6. The method for preparing the absorbing material according to claim 5, characterized in that: In the first mixed solution, the mass ratio of MXene material to natural rubber is 3:
1.
7. The method for preparing the absorbing material according to claim 5, characterized in that: The sponge matrix was immersed in the first mixed solution for 10 minutes.
8. The method for preparing the absorbing material according to claim 5, characterized in that: In the second mixed solution, the mass ratio of MXene material to natural rubber is 3:
1.
9. The method for preparing the wave absorbing material according to claim 5, characterized in that: The temperature of the drying process is 60° C., and the time of the drying process is 1 to 12 hours.
10. Use of the absorbing material according to any one of claims 1 to 4 or the absorbing material prepared by the preparation method according to any one of claims 5 to 9 in the field of electromagnetic wave absorption.
Citation Information
Patent Citations
MXene / natural rubber flexible composite film and preparation method thereof
CN110606998A
Metal carbide terahertz electromagnetic shielding composite material and preparation method thereof
CN112920451A
Self-repairing epoxidized natural rubber composite material and preparation method thereof
CN116218060A
Electromagnetic shielding composite material of impregnated fabric containing MXene nanosheets and rubber film and preparation method of electromagnetic shielding composite material
CN117656615A
Electromagnetic shielding sponge with core-spun structure as well as preparation method and application of electromagnetic shielding sponge
CN118620278A